Impact of Biochemical Characterization of Gliadins of Indian Wheat Varieties: Exploring the Impact of Biochemical Characterization on Gluten Components in Indian Wheat Varieties (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Due to their gluten components which regulate their dough properties, eight varieties of durum wheat-PDW 233, MACS-9, HI-8498, A-9-30-1, Raj 911, Raj 1555 with good quality characteristics and Bijaga yellow, NIDW-15 with poor quality characteristics have been identified. The content of protein in these varieties ranged from 11.1(Yo to 13.8 percent and the content of ~-carotene from 4.1 to 5.85 ppm with maximum in PDW-233 and minimum in A-9-30-1. Only in the good quality durum varieties was a 45 kD polypeptide present. However, PCR amplification of the genomic DNA from the selected varieties using unique primers of the LMW glutenin gene showed no polymorphism between the go